Prediction of lactation persistency in crossbred cattle using genotype profile of lactation curve traits - VOHRA, VIKAS; CHOPRA, ALKA; CHAKRAVARTY, A K (The Indian Journal of Animal Sciences, 2017)
The objective of the present study was to identify the best fit lactation model in relation to bovine leptin gene and to assess lactation persistency based on lactation curve traits in crossbred Karan Fires cattle. Incomplete gamma (Wood) function and exponential (Wilmink) function tests were used to describe the characteristics of lactation curve in first lactation. Woods model showed a comparatively better fit. Different types of lactation curves depicted by these cattle using data spread over a period of 15 years (1994 to 2009) were grouped into desired and nondesired type of lactation curve. Subsequently, genotype profiling was done using PCR-RFLP. A single nucleotide polymorphism identified in exon-2 region of bovine leptin gene, was associated with desired type of lactation curve and animals having TT genotype showed better persistency of milk yield. The results validated in test population had shown positive relationship between leptin genotypes and lactation curve traits. The inference from work has a potential application in breeding program of the country, where it may give support to existing expected producing ability (EPA) based selection methodology followed for selection of dairy animals, by adding leptin genotype as one additional selection criterion for early selection in crossbred dairy bulls and cattle.